In Vivo distribution dynamics of Gold Nanoparticles: A quantitative analysis - Angélica Barbezan; Wilmmer Alexander Rosero; Luis Fernando Almeida; Maria Eduarda Rigo; Fabio Fernando Silva; Maria Elisa Rostelato (Brazilian Journal of Radiation Sciences)
This study evaluated the biodistribution of gum arabic-functionalized gold nanoparticles (GA-AuNPs) in Balb/C Nude mice following intravenous administration. Two activity regimens (200 µCi and 600 µCi) were analyzed at two different time points (3 and 24 hours post-injection). The results showed predominant accumulation of GA-AuNPs in the liver, spleen, and gallbladder, suggesting hepatobiliary excretion as the primary clearance route. A reduction in liver uptake after 24 hours indicates potential nanoparticle metabolism or elimination. Although this study focused on intravenous delivery, previous work from our group using BSA-coated AuNPs administered intratumorally demonstrated higher tumor retention and reduced systemic accumulation, reinforcing the importance of administration route and surface coating in defining nanoparticle biodistribution. These findings contribute to the understanding of how delivery strategy influences nanoparticle bioavailability and support the development of safer and more targeted therapeutic platforms.